A gamification framework to enhance students’ intrinsic motivation on MOOC - Rujianto Eko Saputro; Sazilah Salam; Mohd. Hafiz Zakaria; Toni Anwar (Universitas Ahmad Dahlan, 2019)
Technological development supports the distribution of education to various parts of the world through online education. One of the learning media that supports the distribution of learning is the Massive Open Online Course (MOOC). However, MOOC has a low number of students who complete the course. Therefore, this research proposes a